THE IMPLEMENTATION OF GENRE-BASED APPROACH IN TEACHING ENGLISH AT MTsN KALIJAMBE, SRAGEN - HANI'AH, UMU (2011)
The current study aims at describing the implementation of Genre-based Approach at MTsN Kalijambe Sragen. The objective of the current study is to describe the teaching learning process at MTsN Kalijambe Sragen using Genre-based Approach. In this current study the writer applies at descriptive qualitative research uses ethnographic study as the type of this research. In this research, the data are derived from event, document, and informant. There are three methods of collecting data namely: observation, interview, and document. The techniques for analyzing data are reducing, display, and verifying. The result of this research shows in the learning objectives, model of syllabus, the material of teaching, the classroom procedure, classroom activities and the problem faced by the teacher. The goal of teaching English is to enable the students in understanding English as means of communication and active in practicing English. The classroom procedure consists of two patterns. The first patterns are BKOF, MOT, JCOT, and ICOT. The second patterns are BKOF, MOT, and ICOT. The classroom activities consist of the activities during BKOF, namely asking question and giving explanation. The activity during MOT is giving model text. The activity during JCOT is group work and the activities during ICOT are giving task in the classroom and giving the task as homework. The writer also found the problems faced by the teacher, namely lack of students' activity, student vocabulary and pronunciation, different capability of the student, difficulties in managing the class, and the lack of time. The teacher of MTsN Kalijambe Sragen does not always use the stages of Genre-based Approach in teaching English.